Implants for non-luminal areas

By forming a magnesium fluoride and balun double-layer structure on the surface of the magnesium alloy, the problem of decomposition rate control of the surface of the magnesium alloy is solved, and the implant is better corrosion resistance and mechanical strength are achieved.

JP7663728B2Active Publication Date: 2025-04-16JAPAN MEDICAL DEVICE TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024009048
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-08
Filing Date
2024-01-24
Publication Date
2025-04-16
Estimated Expiration
2040-03-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the decomposition rate of the magnesium alloy surface, resulting in insufficient stability and function maintenance in the body.

Method used

By fluorinating the surface of the magnesium alloy, a first layer of magnesium fluoride is formed, and a second layer of Parylene is formed thereon, thereby controlling the decomposition rate of the surface of the magnesium alloy.

Benefits of technology

The appropriate decomposition control of the surface of magnesium alloy is achieved, providing better corrosion resistance and mechanical strength, and is suitable for implants in non-peptide areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663728000010
    Figure 0007663728000010
  • Figure 0007663728000011
    Figure 0007663728000011
  • Figure 0007663728000001
    Figure 0007663728000001
Patent Text Reader

Abstract

To provide an implant for a non-luminal region with improved corrosion resistance and a method for producing the same.SOLUTION: An implant for a non-luminal region comprises (1) (a) a magnesium fluoride layer and, (b) a parylene layer on a magnesium alloy surface on which a magnesium alloy surface having a predetermined shape is fluorinated to form a fluorinated layer, and a parylene layer is formed on the fluorinated layer. (2) (a) A magnesium alloy surface having an arbitrary shape is fluorinated to form a magnesium fluoride layer, and then (b) a para-xylylene resin is vapor-deposited on the magnesium fluoride layer to form a parylene layer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Related Applications

[0001] This application claims priority to Japanese Patent Application No. 2019-062874 filed on March 28, 2019, and Japanese Patent Application No. 2020-001520 filed on January 8, 2020, the entire contents of which are incorporated herein by reference. [Technical field]

[0002] The present invention relates to an implant for non-luminal regions, which is made of a biodegradable magnesium alloy and has a modified surface by coating the surface of the magnesium alloy with a corrosion-inhibiting layer. The implant for non-luminal areas according to the present invention is used as an implant in orthopedic surgery, oral surgery, plastic surgery, or brain surgery. [Background technology]

[0003] In modern medical technology, implants are widely used as supports for attaching or fixing tissues or bones for surgical purposes. However, implants remaining in the human body after surgery can cause various complications in the human body, and implants after surgery must be removed through additional surgery after the purpose is achieved, which is troublesome. Much research has been conducted to make implant metals from biodegradable materials, and as a result, biodegradable materials made from a variety of materials, including polymer-based materials, ceramic-based materials, and metal-based materials, have been proposed.

[0004] In response to this, there is a strong demand for the development of metallic materials that are strong, easy to process, ductile, and also biodegradable. Magnesium, iron, tungsten, and other materials have been proposed as biodegradable materials, with magnesium attracting attention as the most suitable biodegradable material. Recently, magnesium alloys have begun to be used in some of the fixation screws for bone adhesion, etc.

[0005] On the other hand, the rate of biodegradable materials in vivo must proceed in proportion to the rate of tissue regeneration. However, if the rate of decomposition of magnesium alloys is too fast and they lose stability before damaged tissues can recover, the medical device will not be able to perform its intended function properly. On the other hand, if the rate of decomposition is too slow, problems such as complications will occur. Therefore, control of the rate of decomposition of biodegradable magnesium is an essential factor that must be considered when designing medical devices that use biodegradable magnesium. For this reason, attempts have been made to treat the surface of biodegradable magnesium alloys with an aqueous solution of hydrofluoric acid (fluorination treatment) (Patent Document 1, etc.). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] WO2018 / 139647 Summary of the Invention [Problem to be solved by the invention]

[0007] The inventors have realized that simply treating the magnesium alloy surface with magnesium fluoride to form a magnesium fluoride layer on the magnesium alloy surface as described in the above prior art documents is insufficient to adequately control the decomposition rate of the magnesium alloy surface. Therefore, the problem to be solved by the present invention is to form a magnesium fluoride layer on the surface of a magnesium alloy, and further form a corrosion-inhibiting layer on the magnesium fluoride layer that suppresses the decomposition rate of the magnesium alloy coated with the magnesium fluoride layer, thereby obtaining an implant for non-luminal areas made of a magnesium alloy coated with such a corrosion-inhibiting layer. [Means for solving the problem]

[0008] As a result of intensive research into the above-mentioned problems, the inventors have discovered that by fluoridating the surface of a magnesium alloy to form a magnesium fluoride layer (first layer) on the surface of the magnesium alloy, and then forming a parylene layer (second layer) on the magnesium fluoride layer, the decomposition rate of the magnesium alloy surface can be sufficiently controlled to form a practical implant for non-luminal areas, and have arrived at the present invention.

[0009] The present invention is configured in the following manner. [Aspect 1] A bioabsorbable implant for non-luminal areas having a core structure made of a magnesium alloy having a predetermined shape, a first anticorrosion layer formed on the core structure and mainly composed of a magnesium fluoride layer formed by fluoriding the surface of the magnesium alloy; and a second corrosion protection layer made of parylene formed on the magnesium fluoride layer. By using the above-mentioned magnesium alloy, the surface of the magnesium alloy is fluoridated to form a fluoridation-treated layer, and further forming a parylene layer on the fluoridation-treated layer, the biodegradation rate of magnesium can be controlled within a range suitable for an implant. In the present invention, the non-luminal region refers to a region that is not a biological lumen (blood vessels, lymphatic vessels, ureter, etc.). The fluoride treatment layer and the parylene layer are each preferably formed over the entire surface of the magnesium alloy.

[0010] [Aspect 2] In the implant for a non-luminal region according to embodiment 1, the magnesium alloy contains, by mass%, 0.95 to 2.00% Zn, 0.05% or more but less than 0.30% Zr, 0.05 to 0.20% Mn, and the remainder being Mg and unavoidable impurities; An implant for non-luminal regions, which is a magnesium alloy having an average crystal grain size of 1.0 to 3.0 μm and a grain size distribution with a standard deviation of 0.7 μm or less. Since non-luminal area implants are used for human medical treatment and may be left in the human body for a certain period of time, the magnesium alloy having the above-mentioned configuration is preferable from the viewpoint of safety for the human body. In particular, the magnesium alloy is preferably one that contains unavoidable impurities in a total amount of 30 ppm or less and does not contain rare earth elements or aluminum. The magnesium alloy may have a breaking elongation of 15 to 50% as measured according to JIS Z 2241. The breaking elongation is preferably more than 30%. The magnesium alloy may have a tensile strength of 250 to 300 MPa and a yield strength of 145 to 220 MPa, as measured according to JIS Z2241. The magnesium alloy preferably contains no precipitates with a grain size of 500 nm or more, and more preferably contains no precipitates with a grain size of 100 nm or more.

[0011] [Aspect 3] In the implant for non-luminal area according to the first or second aspect, The magnesium alloy is an implant for a non-luminal area having a shape of a wheel, plate, rod, pipe, band, wire, ring, or a combination of one or more of the above shapes. For implants in non-luminal areas, magnesium alloys having shapes selected depending on the application are used.

[0012] [Aspect 4] The implant for a non-luminal region according to any one of aspects 1 to 3, wherein the implant for a non-luminal region is used for orthopedic surgery, oral surgery, plastic surgery, or brain surgery.

[0013] [Aspect 5] The implant for a non-luminal area according to any one of the first to fourth aspects is used as an implant for a suturing tool such as a clip, a stapler, a wire, or a suture needle, or as an implant for a bone joining member such as a bone pin, a bone screw, or a suture anchor.

[0014] [Aspect 6] 6. The implant for a non-luminal region according to any one of aspects 1 to 5, wherein the magnesium fluoride layer has a thickness of 0.5 to 1.5 μm. In embodiment 6, forming a magnesium fluoride layer on the surface of the magnesium alloy is effective in slowing down the decomposition rate of the magnesium alloy, but it is difficult to form a magnesium fluoride layer with a thickness exceeding 1.5 μm, and it is preferable to appropriately select a thickness within the range of 0.5 to 1.5 μm.

[0015] [Aspect 7] In the implant for non-luminal regions according to any one of aspects 1 to 6, the parylene constituting the parylene layer is formed from parylene N (chemical formula 1 below), parylene C (chemical formula 2 below), parylene M (chemical formula 3 below), parylene F (chemical formula 4 below), parylene D (chemical formula 5 below), or parylene HT (chemical formula 6 below). [ka]

[0016] [Aspect 8] In any one of aspects 1 to 7, The implant for non-luminal regions, wherein the parylene layer has a thickness of 0.05 to 1 μm. In this embodiment, since the parylene layer is formed on the magnesium fluoride layer, it is possible to effectively control the decomposition rate of the magnesium alloy with a thin layer.

[0017] [Aspect 9] In any one of aspects 1 to 8, An implant for non-luminal regions, wherein a biomaterial layer is formed on at least a portion of the surface of the parylene layer, the biomaterial layer being made of at least one biomaterial selected from the group consisting of biodegradable polymers, proteins and calcium phosphate.

[0018] Aspect 10 (1) A method for producing an implant for non-luminal regions, comprising the steps of: (1) fluorinating a surface of a magnesium alloy having any desired shape to form a magnesium fluoride layer on the magnesium alloy surface; and (2) vapor-depositing a polyparaxylylene resin onto the magnesium fluoride layer to form a parylene layer, thereby producing an implant for non-luminal regions, having (1) a magnesium fluoride layer on the magnesium alloy surface; and (2) a parylene layer on the magnesium fluoride layer. The magnesium alloy may have various shapes, such as wheel, plate, rod, pipe, band, wire, ring, or a combination of one or more of the above shapes, depending on the application of the magnesium alloy. The implant for non-luminal region according to the present invention can be manufactured by immersing magnesium alloys of various shapes in an aqueous hydrofluoric acid solution to perform a fluorination treatment, and then forming a parylene layer on the fluoridated layer of the magnesium alloy.

[0019] It should be noted that any combination of at least two elements disclosed in the claims and / or drawings is also included in the present invention. In particular, any combination of two or more of the claims described in the claims is also included in the present invention. Effect of the Invention

[0020] In the first aspect of the present invention, an implant for non-luminal areas obtained by forming a magnesium fluoride layer on a magnesium alloy surface and then forming a parylene layer on the magnesium fluoride layer is provided with corrosion resistance and is capable of maintaining mechanical strength for a predetermined period of time. By forming an additional layer of parylene on the magnesium fluoride layer, a non-luminal implant is provided that has sufficient corrosion resistance for a variety of applications. The magnesium fluoride layer is biodegraded and absorbed in the body, but the parylene layer is not absorbed in the body. By forming a parylene layer on the magnesium fluoride layer, the parylene layer can be made thin, and as a result, the influence of the remaining parylene layer on the body can be reduced. As shown in Comparative Examples 1 and 2 below, parylene alone cannot suppress the elution of magnesium alloys more than magnesium fluoride, but unexpectedly, by combining a magnesium fluoride layer with a parylene layer, the corrosion resistance can be improved more than when magnesium fluoride is used alone. In other words, by covering the first corrosion protection layer with the second corrosion protection layer made of a parylene layer, a synergistic effect is obtained in which the corrosion resistance of the first corrosion protection layer can be maintained for a longer period of time.

[0021] In the second aspect of the present invention, the magnesium alloy is excellent in terms of safety to the human body since it does not contain rare metals and aluminum. The magnesium alloy is an alloy consisting of a single phase of almost complete solid solution type, or has a structure in which fine precipitates containing nanometer-sized Zr are dispersed in the alloy. This magnesium alloy has excellent deformability (ductility, elongation) since the grain size is fine and uniform, and is also excellent in mechanical properties such as tensile strength and yield strength since it does not contain coarse precipitates that can be fracture origins. The magnesium alloy preferably contains, as inevitable impurities, Fe, Ni, Co, and Cu at less than 10 ppm each, and more preferably does not contain Co as an inevitable impurity. An implant for non-luminal areas made of the above-mentioned magnesium alloy has excellent deformation characteristics and its biodegradation characteristics are appropriately controlled.

[0022] In the third aspect of the present invention, the first layer and the second layer formed on the surface of magnesium alloys of various shapes have deformation-following properties and can be used for various applications.

[0023] In the fourth and fifth aspects of the present invention, the implant for non-luminal area according to the present invention is used for various therapeutic applications, and ultimately, the magnesium alloy itself is decomposed and absorbed and integrated with biological tissue, and the parylene layer is thin and thus closely embedded in the biological tissue.

[0024] In the sixth aspect of the present invention, the greater the thickness of the magnesium fluoride layer, the more improved the corrosion resistance is, but it is necessary to consider a balance with the deformation followability of the magnesium fluoride layer.

[0025] In the seventh and eighth aspects of the present invention, the magnesium alloy having a parylene layer formed on a magnesium fluoride layer has a higher effect of suppressing the decomposition rate of magnesium than a magnesium alloy having only a magnesium fluoride layer. Among them, a parylene layer formed from parylene C is preferable in terms of deformation followability. The thickness of the parylene layer is selected within the range of 0.05 to 1 μm, but it is preferable to keep it to a minimum because the parylene layer remains in the living body.

[0026] In the ninth aspect of the present invention, it is preferable that a biomaterial layer (such as a biodegradable polymer layer, a protein layer, or a calcium phosphate layer) is formed on at least a part of the surface of the parylene layer. The biomaterial layer plays a role of improving the delivery of the magnesium alloy product to a predetermined location in the body, protecting the parylene layer from external stress, improving biocompatibility and functionality with respect to biological tissue, and carrying drugs (such as anti-inflammatory agents, sedatives, osteoporosis treatment drugs, and limus-based drugs). The biodegradable polymer layer may be composed of two layers, an inner layer on the parylene layer side and an outer layer on the living body side in contact with the inner layer, and a drug may be contained in either layer.

[0027] According to the tenth aspect of the present invention, a magnesium fluoride layer (first layer) can be formed on the surface of a magnesium alloy of various shapes, and then a parylene layer (second layer) can be formed on top of that, thereby producing an implant for non-luminal areas comprising the first and second layers. [Brief description of the drawings]

[0028] The present invention will be more clearly understood from the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are merely for illustration and description, and should not be used to determine the scope of the present invention, which is determined by the appended claims. [Figure 1] FIG. 2 is a schematic diagram showing components of an implant for non-luminal areas according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing the shape of a sample used in an example showing an example of an implant for a non-luminal area according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] (Implants for non-luminal areas) As shown in Figure 1, one example of an implant (Mg alloy) for non-luminal areas of the present invention comprises a magnesium alloy a having a predetermined shape, a magnesium fluoride (MgF2) layer (first layer) b formed by fluoridating the surface of the magnesium alloy a [the surface contains Mg(OH)2 and the like formed by oxidizing the Mg on the surface and exhibits hydrophilicity], and a parylene layer (second layer) c formed on the magnesium fluoride layer b. The technical elements of the above configuration include an element of selecting a magnesium alloy composition that is biodegradable and adaptable according to the application, an element of forming a magnesium fluoride layer mainly composed of MgF2 on the surface of the magnesium alloy in order to control corrosion of the magnesium alloy having the selected alloy composition, and an element of forming a carbon coating layer (second layer) made of parylene on the surface of the magnesium fluoride alloy layer.

[0030] (Magnesium alloy) Magnesium alloys used in the present invention include the AZ series (Mg-Al-Zn) (AZ31, AZ61, AZ91, etc.), AM series (Mg-Al-Mn), AE series (Mg-Al-RE), EZ series (Mg-RE-Zn), ZK series (Mg-Zn-Zr), WE series (Mg-RE-Zr), AX or AXJ series (Mg-Al-Ca), etc., and among these, magnesium alloys that do not contain aluminum or rare metals that are harmful to the human body, contain 90 mass % or more magnesium, and contain Zn, Zr, and Mn as accessory components are particularly preferred. The magnesium alloy used in the present invention is preferably composed of a magnesium alloy containing 90 mass% or more of magnesium (Mg) as a main component, zinc (Zn), zirconium (Zr) and manganese (Mn) as subcomponents, not containing at least one rare earth element selected from scandium (Sc), yttrium (Y), dysprosium (Dy), samarium (Sm), cerium (Ce), gadolinium (Gd) and lanthanum (La) and not containing aluminum (Al), and containing 30 ppm or less of inevitable impurities selected from the group consisting of iron (Fe), nickel (Ni), cobalt (Co) and copper (Cu). By having such a composition, biological safety and mechanical properties are ensured. In order to improve biological safety and mechanical properties, it is more suitable for the Mg content to be 93 mass % or more, and even more suitable for the Mg content to be 95 mass % or more. By not containing at least one rare earth element selected from the group consisting of Sc, Y, Dy, Sm, Ce, Gd, and La, and by not containing Al, and preferably by not containing any rare earth elements and Al, harmful effects on the human body can be prevented.

[0031] A preferred magnesium alloy in the present invention is a magnesium alloy containing, by mass%, 0.95 to 2.00% Zn, 0.05% or more but less than 0.30% Zr, 0.05 to 0.20% Mn, with the remainder being Mg and unavoidable impurities, and having an average crystal grain size of 1.0 to 3.0 μm with a standard deviation of 0.7 μm or less. In the present invention, by controlling the composition of the magnesium alloy within the above range, advantages are recognized, such as improved plastic workability, and improved properties such as breaking elongation due to the refinement and uniformity of the alloy grain size.

[0032] The magnesium alloy with the above structure can suppress the possibility of fracture during or after deformation because it avoids the formation of coarse precipitates that are the starting point of fracture. Although Zr, which is added to refine the crystal grain size of the alloy, may form precipitates, they are usually nanometer-sized (less than 100 nm) and dispersed in the parent phase, so the effect on deformation and corrosion of the alloy can be almost negligible.

[0033] Zinc (Zn): 0.95% or more, 2.00% or less by mass Zn is added to form a solid solution with Mg and improve the strength and elongation of the alloy. If the amount of Zn added is less than 0.95%, the desired effect cannot be obtained. If the Zn content exceeds 2.00%, the solubility limit is exceeded, Zn-rich precipitates are formed, and the corrosion resistance is reduced, which is undesirable. Therefore, the Zn content is set to 0.95% or more and 2.00% or less. The Zn content may be less than 2.00%.

[0034] Zirconium (Zr): 0.05% or more, less than 0.30% by mass Zr hardly dissolves in Mg, forms fine precipitates, and has the effect of preventing the crystal grain size of the alloy from becoming coarse. If the amount of Zr added is less than 0.05%, the effect of adding the Zr cannot be obtained. If the amount of Zr added is 0.30% or more, the amount of precipitates increases, and the effect of refining the grain size decreases. In addition, the areas where the precipitates are segregated become the starting points for corrosion and destruction. Therefore, the Zr content is set to 0.05% or more and less than 0.30%. The Zr content may be 0.10% or more and less than 0.30%.

[0035] Manganese (Mn): 0.05% or more, 0.20% or less by mass Mn is effective in refining the alloy and improving the corrosion resistance. If the Mn content is less than 0.05%, the desired effect cannot be obtained. If the Mn content exceeds 0.20%, the plastic workability decreases. Therefore, the Mn content is set to 0.05% or more and 0.20% or less. The preferred Mn content is 0.10% or more and 0.20% or less.

[0036] (Inevitable impurities) In magnesium alloys, it is preferable to control the content of unavoidable impurities. Since Fe, Ni, Co, and Cu promote corrosion of magnesium alloys, the content of each is preferably less than 10 ppm, more preferably 5 ppm or less, and preferably substantially not contained. The total amount of unavoidable impurities is preferably 30 ppm or less, more preferably 10 ppm or less. In addition, it is preferable that rare earth elements and aluminum are not substantially contained. Here, if the content in the alloy is less than 1 ppm, it is considered that it is substantially not contained. The content of unavoidable impurities can be confirmed, for example, by ICP emission spectroscopy.

[0037] (Magnesium alloy manufacturing) The above magnesium alloy can be produced by putting Mg, Zn, Zr, and Mn metals or alloys into a crucible, melting them at a temperature of 650 to 800°C, and casting them according to a normal magnesium alloy production method. If necessary, solution heat treatment may be performed after casting. Rare earth elements (and aluminum) are not included in the metal. Furthermore, by using high purity metal, the amount of Fe, Ni, Co, and Cu in the impurities can be suppressed. Fe, Ni, and Co in the impurities may be removed by de-ironization at the molten metal stage. And / or, distilled and refined metal may be used.

[0038] (Metal structure and mechanical properties) By controlling the composition and manufacturing method described above, the magnesium alloy can have a fine and uniform structure with an average crystal grain size of 1.0 to 3.0 μm, for example, 1.0 to 2.0 μm, and a standard deviation of 0.7 μm or less, for example, 0.5 to 0.7, in terms of grain size distribution. The standard deviation is preferably 0.65 μm or less. The fine precipitates containing Zr can have a grain size of less than 500 nm, preferably less than 100 nm. The parent phase excluding the Zr precipitates is preferably a total solid solution of the Mg-Zn-Mn ternary alloy. The alloy has mechanical properties, as measured according to JIS Z2241, of tensile strength of 230 to 380 MPa, for example 250 to 300 MPa, proof stress of 145 to 220 MPa, and breaking elongation of 15 to 50%, for example 25 to 40%. Here, the tensile strength is preferably more than 280 MPa. The breaking elongation is preferably more than 30%.

[0039] (Magnesium alloy shape) The magnesium alloy may have a shape such as a wheel, plate, rod, pipe, band, wire, ring, or a combination of one or more of the above shapes, and the first and second layers are formed using a magnesium alloy having a shape selected depending on the application of the magnesium alloy.

[0040] (Formation of magnesium fluoride layer) A fluorination treatment is performed on the surface of a magnesium alloy having a predetermined shape. The conditions of the fluorination treatment are not particularly limited as long as the MgF2 layer can be formed, but for example, the magnesium alloy can be immersed in a treatment liquid such as a hydrofluoric acid aqueous solution. When immersing, it is preferable to shake the magnesium alloy at 50 to 200 ppm, preferably 80 to 150 ppm. Thereafter, the magnesium alloy on which the MgF2 layer has been formed is taken out and thoroughly washed with a washing liquid (for example, an acetone aqueous solution). The washing is, for example, ultrasonic washing, and when the magnesium alloy is dried after washing, it is preferable to use a method of drying it at 50 to 60°C under reduced pressure for 24 hours or more.

[0041] (Structure of Magnesium Fluoride Layer) The magnesium fluoride layer is composed of magnesium fluoride as a main component. For example, it may be composed of MgF2, which is contained at 90% or more as a main component. Furthermore, it may contain oxides and hydroxides such as MgO and Mg(OH)2 as secondary components. The magnesium fluoride layer may contain oxides and hydroxides of metals other than magnesium that constitute the medical device for the above purpose.

[0042] (Thickness of magnesium fluoride layer) The thickness of the magnesium fluoride layer is preferably 0.5 μm or more in order to exhibit corrosion resistance, and is preferably 3 μm or less in order to exhibit deformation followability.

[0043] (Formation of Parylene layer) In the present invention, by forming a thin second anticorrosive layer made of parylene and having a thickness of 0.05 to 1 μm, preferably 0.08 to 0.8 μm, on the first anticorrosive layer, the corrosion resistance of the magnesium alloy can be significantly improved without impairing bioabsorbability. If the thickness is too thin, the anticorrosive effect tends to be insufficient, and if the thickness is too thick, the bioabsorbability tends to be impeded. Parylene is a general term for paraxylylene or its derivatives, and examples thereof include parylene N [formula (1) below] with no functional group in the aromatic ring, parylene C [formula (2) below] in which one of the aromatic ring hydrogens is substituted with chlorine, parylene M [formula (3) below] in which one of the aromatic ring hydrogens is substituted with a methyl group, parylene F [formula (4) below] in which one of the methylene groups of parylene M is fluorinated, parylene D [formula (5) below] in which the hydrogens at the 2- and 5-positions of the aromatic ring of parylene N are substituted with chlorine, and parylene HT [formula (6) below] in which both methylene groups of parylene N are fluorinated. These parylenes are commercially available, and for example, both parylene N and parylene C can be obtained from Daisan Chemical Co., Ltd. [ka]

[0044] (Parylene layer thickness) In the present invention, by forming a thin parylene layer having a thickness of 0.05 to 1 μm on a magnesium fluoride layer, the corrosion resistance of the Mg alloy can be significantly improved without impairing biodegradability. If the thickness is too thin, the corrosion prevention effect tends to be insufficient, and if the thickness is too thick, the biodegradability tends to be impeded.

[0045] (biomaterial layer) In the present invention, a biomaterial layer such as a biodegradable polymer, a protein, or calcium phosphate may be formed on the entire surface or a part of the surface of the parylene layer. Examples of biodegradable polymers include polyesters, such as poly-L-lactic acid (PLLA), poly-D,L-lactic acid (PDLLA), polylactic acid-glycolic acid (PLGA), polyglycolic acid (PGA), polycaprolactone (PCL), polylactic acid-ε-caprolactone (PLCL), polyglycolic acid-ε-caprolactone (PGCL), poly-p-dioxanone, polyglycolic acid-trimethylene carbonate, and poly-β-hydroxybutyric acid. Examples of proteins include collagen, gelatin, and fibroin. Examples of calcium phosphate include hydroxyapatite, β-tricalcium phosphate, and octacalcium phosphate.

[0046] (Drugs) Depending on the therapeutic purpose for which the non-luminal implant of the present invention is to be used, the biomaterial layer may contain a medicinal agent.

[0047] (Medical Use) The obtained implant for non-luminal area is utilized for patient treatment as an alloy for orthopedic implant, oral surgery implant, plastic surgery implant, or brain surgery implant. Specific examples include alloys for suturing tools such as clips, staplers, wires, and suture needles, and alloys for bone joining members such as bone pins, bone screws, and suture anchors. EXAMPLES

[0048] (Magnesium alloy manufacturing examples 1 and 2) High purity ingots of Mg, Zn, Mn, and Zr were prepared as materials. These were weighed to have the component concentrations listed in Table 1, and were put into a crucible, melted at 730°C, and the stirred melt was cast into an ingot, and magnesium alloys of Production Example 1 and Production Example 2, in which the blending ratio of the main components was within the range of the present invention, were obtained. The raw materials used did not contain rare earth elements or aluminum as unavoidable impurities. The magnesium ingot used had a purity of 99.99% and a low concentration of the impurity Cu, and de-ironization was performed in the furnace to remove iron and nickel from the molten metal. The impurity concentrations of the samples obtained in this way were measured using an ICP emission spectrometer (AGILENT, AGILENT 720 ICP-OES). The components of Production Example 1 and Production Example 2 are shown in Table 1. The concentrations of Fe, Ni, and Cu were all 8 ppm or less (Ni and Cu were 3 ppm or less), Al and rare earth elements were not detected, and Co was below the detection limit. The total impurity concentration is 11 to 12 ppm.

[0049] [Table 1]

[0050] [Mechanical property measurements] For each of the alloys in the above manufacturing examples, round bars were prepared by hot extrusion, and the tensile strength, yield strength, and breaking elongation were measured in accordance with JIS Z 2241. The results are shown in Table 2.

[0051] [Table 2]

[0052] (Mg alloy manufacturing example 3) High purity ingots of Mg, Zn, Mn, and Zr were prepared as materials. Each of these was weighed to have the component concentrations listed below, and placed in a crucible, melted and stirred at 730°C, and the resulting molten material was cast into an ingot. The raw materials used did not contain rare earth elements or aluminum, even as unavoidable impurities. The magnesium ingot used had a purity of 99.9% and a low concentration of Cu impurities. De-ironization was also carried out in the furnace to remove iron and nickel from the molten metal. The impurity concentration of the obtained ingot was measured using an ICP optical emission spectrometer (AGILENT 720 ICP-OES, manufactured by AGILENT Corporation). The component concentrations (mass%) of the obtained ingot are as follows, and aluminum and rare earths are not contained. Mg balance, Zn 1.5%, Mn 0.4%, Zr 0.4%, The above ingot contained inevitable impurities of Fe, Ni, Co and Cu in the following concentrations. Fe 5ppm, Ni 5ppm, Co ND (below detection limit), Cu 1ppm

[0053] (Magnesium plate manufacturing) The magnesium alloy ingot of Production Example 3 was machined into the shape shown in FIG. 2 (thickness: 1 mm) (the dimensions shown in FIG. 2 are in mm) to obtain a magnesium alloy substrate A. The magnesium alloy ingot of Production Example 3 was machined into a disk shape (diameter 50 mm×thickness 1 mm) to prepare a magnesium alloy substrate B.

[0054] (Electrolytic polishing of magnesium alloy substrate) The oxides adhering to the surface of the obtained magnesium alloy substrate were removed with an acidic solution. Then, the anode was immersed in the electrolyte and connected to the metal plate serving as the cathode via a DC power source, and the magnesium alloy substrate serving as the anode was mirror-polished to obtain a smooth surface by applying a voltage. In order to stabilize the mucus layer during voltage application, the electrolyte was stirred while controlling the temperature to be constant. In addition, in order to suppress the generation of bubbles at the cathode, the application and disconnection of the voltage was appropriately repeated. Note that if bubbles liberated from the cathode adhere to the magnesium alloy substrate, this will cause poor surface accuracy. The obtained magnesium alloy substrate with mirror-like surface was used to prepare samples shown in the following examples and comparative examples.

[0055] (Weight Residual Rate and Tensile Strength Residual Rate Evaluation Method) The obtained samples were immersed in a plasma simulant solution (EMEM + 10% FBS), then immersed and shaken at 100 rpm in a 37°C, 5% CO2 atmosphere. After 28 days of immersion, the extracted samples were ultrasonically cleaned with chromic acid to completely remove corrosion products such as magnesium hydroxide, and the weight remaining rate before and after immersion was evaluated (n=5). On the other hand, the obtained samples were similarly immersed and shaken for 28 days, after which the extracted samples were washed to remove the corrosion products, and then chucked in a tensile testing machine and subjected to a tensile test at a crosshead speed of 5 mm / min to evaluate the remaining tensile strength before and after immersion (n=5).

[0056] Example 1 Magnesium alloy substrate A with mirror-like texture was immersed and shaken at 100 rpm in a 27M aqueous solution of hydrofluoric acid. After 24 hours, the sample extracted was thoroughly ultrasonically cleaned with water and acetone, and then dried at 60°C under reduced pressure for 24 hours to obtain a sample with a magnesium fluoride layer (thickness 1 μm) formed. A 500 nm thick parylene C layer was formed on this sample by the CVD method to obtain a sample with a parylene layer on the magnesium fluoride layer.

[0057] Example 2 A sample obtained by the same method as in Example 1 was immersed in a 1% solution of 1% polylactic acid in THF for 3 minutes. The sample was taken out of the solution and dried at 60°C under reduced pressure for 24 hours to obtain a sample having a magnesium fluoride layer, a parylene layer, and a polylactic acid layer in this order.

[0058] Comparative Example 1 Magnesium alloy substrate A with mirror-like texture was immersed and shaken at 100 rpm in a 27M aqueous solution of hydrofluoric acid. After 24 hours, the sample extracted was thoroughly ultrasonically cleaned with water and acetone, and then dried at 60°C under reduced pressure for 24 hours to obtain a sample on which a magnesium fluoride layer (thickness 1 μm) was formed.

[0059] Comparative Example 2 A sample was obtained by forming a 500 nm-thick parylene C layer by CVD on a magnesium alloy substrate A (not fluorinated) with a mirror surface.

[0060] Comparative Example 3 A sample obtained in the same manner as in Comparative Example 2 was immersed in a 1% solution of 1% polylactic acid in THF for 3 minutes. The sample was taken out of the solution and dried at 60°C under reduced pressure for 24 hours to obtain a sample having a polylactic acid layer on a parylene layer.

[0061] The results of measuring the weight residual rate of the above samples are shown in Table 3, and the results of measuring the tensile strength residual rate are shown in Table 4. The weight of the sample before immersion was 0.36±0.1 g, and the tensile strength before immersion was 310±10 MPa.

[0062] [Table 3]

[0063] [Table 4]

[0064] The samples according to the present invention (Examples 1 and 2) had a significantly smaller rate of decrease in weight and tensile strength than the sample not having a parylene layer (Comparative Example 1) and the samples not having a magnesium fluoride layer (Comparative Example 2 and Comparative Example 3), suggesting that the two-layer structure of the magnesium fluoride layer and the parylene layer provides an excellent corrosion prevention effect.

[0065] (Inflammatory evaluation method using subcutaneous implantation in mice) A sample with excellent corrosion resistance can suppress inflammatory reactions caused by corrosion in biological tissues, and therefore the corrosion resistance of a sample can be understood by evaluating the inflammatory properties of tissues. The obtained test samples were implanted subcutaneously into the backs of mice (2 pieces / mouse), and the inflammation of the tissue was scored on the following 4-point scale on the 60th day (n=5). [Table 5]

[0066] Example 3 Magnesium alloy substrate B with mirror-like texture was immersed and shaken at 100 rpm in a 27M aqueous solution of hydrofluoric acid. After 24 hours, the sample extracted was thoroughly ultrasonically cleaned with water and acetone, and then dried for 24 hours at 60°C under reduced pressure to obtain a sample with a magnesium fluoride layer (thickness 1 μm). A 500 nm thick parylene C layer was formed on this sample by CVD, obtaining a sample with a parylene layer on the magnesium fluoride layer.

[0067] Example 4 A sample obtained in the same manner as in Example 3 was immersed in a 1% solution of 1% polylactic acid in THF for 3 minutes. The sample was taken out of the solution and dried at 60°C under reduced pressure for 24 hours to obtain a sample having a polylactic acid layer on the magnesium fluoride layer and the parylene layer.

[0068] Comparative Example 4 Magnesium alloy substrate B with mirror-like texture was immersed and shaken at 100 rpm in a 27M aqueous solution of hydrofluoric acid. After 24 hours, the sample was taken out of the solution, thoroughly ultrasonically cleaned with water and acetone, and then dried at 60°C under reduced pressure for 24 hours to obtain a sample on which a magnesium fluoride layer (thickness 1 μm) was formed.

[0069] Comparative Example 5 A sample was obtained by forming a 500 nm-thick parylene C layer by CVD on a magnesium alloy substrate B (not fluorinated) with a mirror surface.

[0070] Comparative Example 6 A sample obtained in the same manner as in Comparative Example 5 was immersed in a 1% solution of 1% polylactic acid in THF for 3 minutes. The sample was taken out of the solution and dried at 60°C under reduced pressure for 24 hours to obtain a sample having a polylactic acid layer on a parylene layer.

[0071] The inflammatory evaluation results of the samples obtained in Examples 3 and 4 and Comparative Examples 4 to 6 are shown in Table 5. [Table 6]

[0072] The samples according to the present invention (Examples 3 and 4) had significantly lower tissue inflammation scores than the sample not having a parylene layer (Comparative Example 4) and the samples not having a magnesium fluoride layer (Comparative Example 5 and Comparative Example 6), suggesting that the two-layer structure of the magnesium fluoride layer and the parylene layer provides excellent corrosion prevention effects. [Industrial Applicability]

[0073] INDUSTRIAL APPLICABILITY The present invention contributes to the development of medical technology by providing an implant for non-luminal areas having a magnesium fluoride layer and a parylene layer formed on the magnesium fluoride layer, which are effective in delaying the decrease in mechanical strength associated with accelerated corrosion of magnesium alloy structures, and thus has extremely high industrial applicability.

[0074] Although the preferred embodiment has been described above with reference to the drawings, a person skilled in the art would easily imagine various changes and modifications within the obvious range by looking at the specification and drawings. Therefore, such changes and modifications are interpreted as falling within the scope of the invention from the claims. [Explanation of symbols]

[0075] a Mg alloy b First coating layer (magnesium fluoride layer) c Second coating layer (parylene layer)

Claims

1. A bioabsorbable implant having a core structure made of a magnesium alloy having a predetermined shape, a first anticorrosive layer formed on the core structure and mainly composed of a magnesium fluoride layer formed by fluoriding the surface of the magnesium alloy; a second anticorrosive layer made of parylene formed on the magnesium fluoride layer; The magnesium alloy contains, in mass%, 0.95 to 2.00% Zn, 0.05 to 0.30 % Zr, 0.05-0.20% Mn, and the balance being Mg and unavoidable impurities; An implant for non-luminal regions, wherein the content of each of Fe, Ni, Co, and Cu as the unavoidable impurities is less than 10 ppm.

2. The implant for non-luminal areas according to claim 1, The total amount of the inevitable impurities, Fe, Ni, Co, and Cu, is 10 ppm or less. Implants for non-luminal areas.

3. The implant for non-luminal area according to claim 1 or 2, The non-luminal area implant comprises: (1) Implants for non-luminal areas, for suturing instruments such as clips, staplers, wires, suture needles, etc.; or (2) for bone suturing components such as bone pins, bone screws, suture anchors, etc.

4. The implant for non-luminal area according to any one of claims 1 to 3, The magnesium alloy is an implant for a non-luminal region, the magnesium alloy having an average crystal grain size of 1.0 to 3.0 μm and a grain size distribution with a standard deviation of 0.7 μm or less.

5. The implant for non-luminal area according to claim 1 or 2, An implant for non-luminal areas, wherein the magnesium alloy has a shape of a wheel, plate, rod, pipe, wire, ring, or a combination of one or more of the above shapes.

6. The implant for non-luminal area according to any one of claims 1 to 5, The implant for a non-luminal region is used for orthopedic surgery, oral surgery, plastic surgery, or brain surgery.

7. 7. The implant for a non-luminal region according to claim 1, wherein the magnesium fluoride layer has a thickness of 0.5 to 1.5 μm.

8. The implant for non-luminal area according to any one of claims 1 to 7, The parylene layer is formed from parylene N (chemical formula 1 below), parylene C (chemical formula 2 below), parylene M (chemical formula 3 below), parylene F (chemical formula 4 below), parylene D (chemical formula 5 below), or parylene HT (chemical formula 6 below). 【Chemistry 1】

9. The implant for non-luminal area according to any one of claims 1 to 8, An implant for a non-luminal region, wherein the parylene layer has a thickness of 0.05 to 1 μm.

10. The implant for a non-luminal region according to any one of claims 1 to 9, An implant for a non-luminal region, wherein a biomaterial layer is formed on a portion of the surface of the parylene layer, the biomaterial being selected from the group consisting of biodegradable polymers, proteins, and calcium phosphate.

11. A method for manufacturing an implant for a non-luminal region, comprising: (1) fluorinating a surface of a magnesium alloy having an arbitrary shape to form a magnesium fluoride layer on the magnesium alloy surface; and (2) vapor-depositing a paraxylylene resin onto the magnesium layer to form a parylene layer, the method comprising the steps of: The magnesium alloy contains, by mass%, 0.95 to 2.00% Zn, 0.05% or more but less than 0.30% Zr, 0.05 to 0.20% Mn, and the balance being Mg and unavoidable impurities, the unavoidable impurities each containing less than 10 ppm Fe, Ni, Co, and Cu, The method for manufacturing an implant for a non-luminal region, wherein the implant for a non-luminal region is for (1) a suturing instrument such as a clip, a stapler, a wire, or a suture needle, or (2) a bone joining member such as a bone pin, a bone screw, or a suture anchor.

Citation Information

Patent Citations

  • Method for manufacturing medical implants from magnesium alloy

    JP2014533967A

  • Bioabsorbable Stent With Hydrothermal Conversion Film and Coating

    US20140277396A1

  • Magnesium alloy

    WO2018131476A1

  • High performance bioabsorbable stent

    WO2018139647A1